Milk protein genes polymorphism in indigenous and crossbred cattle from a private dairy farm in Ethiopia - Tewodros, R.; Meseret, Selam; Mohammed, S.; Dadi, H.; Nigussie, H. (African Journals Online, 2024)
Kappa casein and beta lactoglobulin genes are major milk proteins which have a direct effect on protein content in dairy cattle. Molecular-based selection through the identification of genetic polymorphism of major protein genes can be used to gain genetic improvement of milk protein yield. The objective of this study was to identify kappa casein (CSN3) and beta lactoglobulin (LGB) genes polymorphisms in indigenous and crossbreed cattle. A total of 90 whole blood samples were collected from individual animal in a private dairy farm. DNA extraction and quality assessment were done salting out procedure and gel electrophoresis, respectively. Polymerase chain reaction (PCR) was performed with gene specific primers. For genotyping, PCR products of CSN3 gene was digested with HinfI and HindIII while LGB gene was digested with HaeIII restriction enzymes. Two haplotypes A and B; three genotypes, AA, AB and BB were observed at CSN3 of HinfI site and LGB HaeIII site, but only AA and AB were observed at CSN3 of HindIII site in crossbred and indigenous cattle populations. However, at CSN3 locus, A allele was found to be more common (0.65) in indigenous cattle than the B allele (0.35), while B (0.51) allele and AB genotype (0.81) were more frequent in crossbred cattle. But, LGB B allele was higher in indigenous cattle (0.67) compared to Allele A (0.33). LGB BB genotype (0.57) is higher followed by AA genotype in indigenous cattle while both allele and genotypic frequencies are equal in crossbred cattle. Both CSN3 and LGB loci were polymorphic in studied populations. Expected heterozygosity was higher in crossbred (0.49, 0.50) than in indigenous (0.38, 0.33) cattle at CSN3 and LGB locus, respectively which might be due to breed variation. The current findings showed that both CSN3 and LGB genes could be promising diagnostic markers in selecting dairy cattle breed. However, further investigations with large sample size and association study with milk composition is required to substantiate the current result.